Natural radioactivity Measurements of Dur-Kurigalzu's Ziggurat, Baghdad Governorate-Iraq using HPGe detector - Hassan, Saja Faez; Al-Alaway, Iman Tarik (Iraqi Journal of Science, 2023)
Measurement of 238U, 233Th and 40K concentrations in soil samples collected from Ziggurat of Dur-Kurigalzu west region of Baghdad, have been evaluated, using high purity germanium detector. The activity concentrations of 238U, 233Th and 40K varied from 16.040  to 26.620 , 14.510  to 31.480 , and 153.820  to 266.320  with average values of 20.604±2.9 , 24.534±3.3 , 212.22±25.1 , respectively. The importance of these measurements lies in the estimation of radiation risk, radium equivalent, absorbed dose, annual effective dose, risk indices, gamma index, and cancer risk. The average value of the absorbed dose ranged from 33.187  outdoors to 63.111  indoors. The mean annual effective dose value was estimated to be 0.043  outdoors and 0.310  indoors from the study area. The total calculated lifetime risk of cancer ranged from 0.991×10-3 to 1.485×10-3, while the indoor lifetime cancer risk exceeded the recommended limit in samples 6, 8, 9, and 10.  The areas examined in this study showed radioactive contamination less than the internationally permissible limits for the sites inhabited by the population.